Foreword. (Musicology of Lithuania / Lietuvos muzikologija, 2014)
An introduction is presented in which the author discusses various reports within the issue on topics including the methods of tenor Virgilijus Noreika in music teaching, the tonal hierarchies in music psychology and the baroque musical context of playing harpsichord.